Microrganismos degradadores de petróleo isolados e solos rizosfericos da província petrolífera de Urucu, Coari, Amazonas - Lima, Dannielle Cordeiro Ribeiro de (2010)
PETROLEUM DEGRADING MICROORGANISMS ISOLATED FROM RHIZOSPHERE SOILS OF ANNATTO OIL PROVINCE, COARI, AMAZON. Universidade do Estado do Amazonas. Rua Carvalho Leal, No. 1777 CEP: 69055-001. Manaus - AM, RIBEIRO-LIMA, Dannielle, C. & OLIVEIRA, Luis A. dannielle.cordeiro@gmail.com. Key words: biodegradation, microbial ecology, oil. Financial support: CNPq The activities related to petroleum exploration have brought great concern given the risks of accidental spills. Province Urucu Oil is being held exploration and production of oil and natural gas. The oil is transported from Urucu wells for the central plant via a pipeline built in 1997. Over time the pipeline can wear out, and there may be leaks and possible contamination in the environment. The aim of this study was to evaluate the occurrence of microorganisms with potential to degrade oil in the rhizosphere of plants around pipelines in Base Operations Geologist Pedro de Moura. Four samples were taken from rhizosphere soil at two different times are obtained from plants around the pipeline, two grass species (Brachiaria humidicola Brachiaria decumbens), a legume (Mucuna pruriens) and a seal (Vismia guianensis). Among the four species collected around pipelines in BOGPM, B. decumbens had the highest occurrence of oil degrading microorganisms. The highest concentration of CFU of bacteria, fungi and yeasts occurred in the dry season. In the rainy season and enriched treatment, the highest concentration of CFU of bacteria occurred in B. humidicola and filamentous fungi and yeasts in M. prurinens. In the dry period and enriched treatment, the highest concentration of CFU of bacteria occurred in B. decumbens, filamentous fungi in M. pruriens and yeast in B. decumbens. The presence of microorganisms capable of biodegrading the oil in DCPIP test indicated that 61.32% are capable of degradation of oil in a period of 120 hours (5 days), and in greater than 120 hours, it was found that 83% of microorganisms isolated have this capability. These results allowed to show that microorganisms associated with rhizosphere of species have the capacity to use oil as a carbon source, indicating which have the potential to degrade oil in the event of a contamination by this product at Amazon.